2009
DOI: 10.5551/jat.1230
|View full text |Cite
|
Sign up to set email alerts
|

Association between Arterial Stiffness and Estimated Glomerular Filtration Rate in the Japanese General Population

Abstract: Aim: Chronic kidney disease (CKD) is associated with an increased risk of cardiovascular disease, although it has yet to be established whether CKD is an independent risk factor for arterial stiffness in community residents. The purpose of this study was to determine the correlation between the cardio-ankle vascular index (CAVI) and estimated glomerular filtration rate (eGFR) in the general population. Methods: We studied 881 consecutively enrolled subjects undergoing health checkups. CAVI was calculated autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 31 publications
3
49
3
2
Order By: Relevance
“…Moreover, previous studies have established a strong association between the CAVI and small-vessel disease of other organs. 23,24 Kubozono et al 23 reported a relationship between the CAVI and a low estimated glomerular filtration rate. Kim et al 24 identified a correlation between the CAVI and microvascular complications in type 2 diabetes mellitus patients without a history of macrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have established a strong association between the CAVI and small-vessel disease of other organs. 23,24 Kubozono et al 23 reported a relationship between the CAVI and a low estimated glomerular filtration rate. Kim et al 24 identified a correlation between the CAVI and microvascular complications in type 2 diabetes mellitus patients without a history of macrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the current analysis, we found that the SBP, DBP and pulse pressure values were higher in the high arterial stiffness group than in the low arterial stiffness group. The CAVI correlates independently with the estimated GFR in the general Japanese population 24) , whereas, in renal insufficiency patients, the CAVI values are closely associated with the cystatin C levels 25) . Another report noted a significant correlation between the serum cystatin C level and the CAVI only in women in a non-chronic kidney disease population 26) .…”
Section: Discussionmentioning
confidence: 99%
“…A GFR < 60 mL/min/1.73 m 2 , which is associated with a gradual increase in the risk for CVD, ESRD, and mortality, is the threshold value for the definition of CKD 8) . CKD has been linked with arterial stiffness in the Japanese general population 9) and a low eGFR and pronounced albuminuria have been found to independently predict mortality and ESRD 10) ; moreover, reduced eGFR has been identified as a predictor of CVD and all-cause mortality in Japan 11) . eGFR is also used, along with urinary protein (albumin) quantification and determination of the primary disease, in CKD severity classification, which determines the risk for CVD and ESRD, as well as mortality 1) .…”
Section: Discussionmentioning
confidence: 99%